2020
DOI: 10.1111/ppc.12450
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep quality, using social media platforms, and academic performance among university students

Abstract: Purpose: Explore the quality of sleep and investigate the relationship between sleep quality, using social media platforms, and academic performance among university students.Design and Methods: A cross-sectional correlation design was used, 412 students completed an electronic questionnaire.Findings: The majority of university students suffer from poor quality of sleep. The most frequently used social media platforms were WhatsApp, Snapchat, and YouTube. The strongest predictor of having very poor sleep quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Our results establish that aromatherapy applied through lavender stone reduces the level of fatigue in the students. In the literature, it has been reported that sleepiness and fatigue are frequent in students during the day owing to the lack of sufficient rest due to insomnia 28–30 . Therefore it is expected that with the effect of aromatherapy, fatigue levels of students would decrease because of increased sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Our results establish that aromatherapy applied through lavender stone reduces the level of fatigue in the students. In the literature, it has been reported that sleepiness and fatigue are frequent in students during the day owing to the lack of sufficient rest due to insomnia 28–30 . Therefore it is expected that with the effect of aromatherapy, fatigue levels of students would decrease because of increased sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has indicated that nursing students have a high prevalence of poor sleep quality, with insomnia being the main problem [32]. These sleep problems in nursing students could be attributed to factors such as prolonged Internet use [33], study at night, stress due to exams, coursework or clinical situations [34] and clinical shift work [35].…”
Section: Discussionmentioning
confidence: 99%
“…The researcher diagnosed sleep disorders in 24% of students, among whom two-thirds suffered from insufficient sleep or late sleep, while 6% suffered from insomnia. Other studies have indicated high prevalence rates of low sleep quality among university students (Almojali, Almalki, Alothman, Masuadi, & Alaqeel, 2017;Thomas & Sundar, 2019;Abu-Snieneh, Aroury, Alsharari, Al-Ghabeesh, & Esaileh, 2020).…”
Section: Introductionmentioning
confidence: 94%